The Economic Benefits of Regulation: Evidence from Professional Tax Preparers - Ayres, Frances L.; Jackson, Betty R.; Hite, Peggy S. (The Accounting Review, 1989)
[An area of concern to tax policymakers is the role of third-party preparers in income tax reporting. This research examines the degree of consistency in judgments of preparers subject to differing degrees of governmental regulation. Economic theory of regulation suggests that CPAs, who are subject to a higher degree of government regulation, would be expected to recommend and justify more pro-taxpayer positions in ambiguous areas of tax law than would unlicensed preparers. This hypothesis was tested by administering a set of tax cases with a high degree of uncertainty regarding the correct tax status to groups of CPA and non-CPA tax practitioners. CPAs were found to be consistently more pro-taxpayer than were non-CPAs.]